x=2.61 radians
Step-by-step explanation
![2\cos (x)+\sqrt[]{3}=0](https://img.qammunity.org/2023/formulas/physics/college/j90r97cjxhgqdxvg72sia5n3krt2h0ujpd.png)
Step 1
Let's isolate x
a)
![\begin{gathered} 2\cos (x)+\sqrt[]{3}=0 \\ \text{subtract }\sqrt[]{3}\text{ in both sides} \\ 2\cos (x)+\sqrt[]{3}-\sqrt[]{3}=0-\sqrt[]{3} \\ 2\cos (x)=-\sqrt[]{3} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/km7a6adwbzdif8qno69vyo4001eg6e765u.png)
Step 2
b) now, divide both sides by 2
![\begin{gathered} 2\cos (x)=-\sqrt[]{3} \\ \text{divide both sides by 2} \\ (2\cos(x))/(2)=\frac{-\sqrt[]{3}}{2} \\ \cos (x)=\frac{-\sqrt[]{3}}{2} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/6dw26bjo81flyic0udtqhf44n1zt2li184.png)
Step 3
c) finally,Inverse cosine in both sides ( remember we are looking for an angle)
![\begin{gathered} \cos (x)=\frac{-\sqrt[]{3}}{2} \\ \text{ Inverse cosine in both sides} \\ \cos ^(-1)(\cos (x))=\cos ^(-1)(\frac{-\sqrt[]{3}}{2}) \\ x=\cos ^(-1)(\frac{-\sqrt[]{3}}{2}) \\ x=\cos ^(-1)(-0.86) \\ x=2.61\text{ radians} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/7skcivnucwc52ue8g5b68j636msc42ifdr.png)
therefore, the answer is
x=2.61 radians
I hope this helps you